(untitled) (Bangladesh Agronomy Journal, 2015)
An intercropping experiment was conducted in the farmers field at Farming Systems Research and Development (FSRD) Site, Kushumhati, Sherpur in sandy loam soil of medium high land during rabi season 2011-12 to observe the productivity and economic feasibility of intercropping systems as compare3d to sole crop (viz. maize + potato, maize + Radish, maize-+-coriander, maize + bushbean, maize + spinach, maize + lalshak and maize sole). The result indicated that grain yield of maize was reduced due to intercropping systems but this reduction was compensated by intercropped. The highest grain yield of maize was found from sole maize (10.90 t ha-1) and lowest (9.32 t ha-1) from intercropped with potato. The maximum maize equivalent yield (14.04 t ha-1), gross return (Tk.10,5300/ha),gross margin (Tk. 75,527/ ha), and benefit cost ratio (BCR) (3.54) was obtained from maize + bushbean intercropping systems which was adventitious over sole maize cropping. Bangladesh Agron. J. 2015, 18(1): 49-52